PENGUKURAN MIKROKLIMAT PERKOTAAN BERBASIS SENSOR CERDAS STUDI KASUS PERUBAHAN SUHU DAN KELEMBABAN DI KENDARI - Hiromi, Rahma; Efendi, Rustam; Alwan, Alwan; Padar, Sekar Alim; Syahrir, Edy Abdurrahman; Taridalla, Sabrilah; Arifin, Arifin (Jurusan Teknik Perencanaan Wilayah dan Kota, Fakultas Sains dan Teknologi, Universitas Islam Negeri Alauddin Makassar, 2026)
Rapid urbanization and climate change exacerbate the urban heat island (UHI) effect, which challenges environmental quality in tropical cities. However, empirical studies on microclimates in medium-sized cities are still limited. This study aims to analyze variations in air temperature and relative humidity in four types of land use (education, housing, terminals, markets) in Baruga District, Kendari, and identify the contributing factors. A quantitative and experimental field approach was used by measuring temperature and humidity at 30 points using data loggers. Measurements were taken during the day and afternoon for two weeks, then analyzed using descriptive statistics, One-Way ANOVA, and Tukey HSD test. The results showed significant temperature differences during the day (F(3, 116) = 4.21, p = 0.007), with the market area being the hottest (34.50°C) and the terminal being the coolest (32.18°C). Areas with large green spaces (education and residential) were cooler. There were no significant differences in the afternoon or in relative humidity. In conclusion, land use significantly affects the urban microclimate during the day. Impervious surfaces increase temperature, while vegetation plays a crucial role in UHI mitigation. This emphasizes the importance of integrating green spaces into tropical urban planning.